Metabolite Profiling, through LC-ESI/LTQOrbitrap/MS Analysis, of Antioxidant Extracts from Physalis alkekengi L. - Maria Assunta Crescenzi; Gabriele Serreli; Monica Deiana; Carlo I. G. Tuberoso; Paola Montoro; Sonia Piacente (Antioxidants, 2023)
Due to the increasing use of Physalis alkekengi L. as a food supplement and starting material for tea preparation, a comprehensive analysis of green extracts was performed. Two different extraction methods were applied to yellow Physalis alkekengi L. fruit and calyx and compared: hydroalcoholic extraction and decoction. Characterization of the metabolome of the calyx and fruit of yellow Physalis alkekengi L. was performed by LC-ESI/LTQOrbitrap/MS followed by LC-ESI/LTQOrbitrap/MS/MS to identify 58 phytocompounds using the two different extraction techniques. Subsequently, through preliminary spectrophotometric assays followed by cell studies, the antioxidant activity of the different Physalis alkekengi L. extracts were evaluated. It was found that Physalis alkekengi L. extracts are a good source of metabolites such as flavonoids, organic acids, phenylpropanoids, physalins and carotenoids, with various biological activities, in particular, antioxidant activity capable of reducing the production of free radicals in intestinal Caco-2 cells. For the first time, an integrated approach (metabolomics approach and antioxidant evaluation) was applied to the study of Physalis alkekengi green extracts and decoctions, the green extraction method mostly used in herbal preparations. An interesting finding was the high antioxidant activity shown by these extracts.